Comprendre le développement humain comme un processus écologique de traduction - Stéphane Simonian; Quentin Magogeat
Two interdependent phenomena are questioned : what allows, ecologically, the subject-environment relation then, the dynamics of this relation. To do this, two scientific currents are mobilized : affordance in its current meaning and the sociology of translation. While each of these currents has its own semantics and epistemology, both initiate breaks in the way of understanding what occurs within human activity and contribute to an ecological approach based on a fundamental principle : all human activity is situated and dynamic, characterizing the processes implemented by the actors according to the properties, in part, perceived of their socio-cultural environment. All deterministic logic is then set aside to place, on the same plane, all the dynamic entities within an environment, whether or not they are perceived by the actors on the ground.